Self‐Regulated Learning Strategies in Computer Programming Education - Ramírez‐Echeverry, Jhon Jairo; Restrepo‐Calle, Felipe; Jiménez, Stephanie Torres (European journal of education, 2025)
ABSTRACT This study investigates the self‐regulated learning strategies employed by students in computer programming courses. Utilising the Questionnaire on Learning Strategies in Computer Programming (CEAPC), the research aims to identify specific strategies used by students. The findings reveal a variety of effective learning strategies, including problem‐solving, knowledge acquisition and study environment management in the context of computer programming learning. However, difficulties in idea organisation were noted, suggesting a need for enhanced support in structuring and documenting thought processes and code. The study also highlights the interdependence of learning strategies, particularly the role of metacognition in conjunction with practice, problem‐solving and time management. Differences in strategy use across course levels and gender were observed, with advanced courses prompting more complex strategies and female students excelling in structured and collaborative learning. These insights provide educators with valuable guidance for developing targeted interventions to improve students' self‐regulated learning abilities in programming education.